Combined application of Trichoderma harzianum and Alcaligenes sp. strain AMB 8 for controlling nursery rot disease of black pepper - T.P. MANOMOHANDAS1, K.N. ANITH* and (Indian Phytopathology, 2002)
Trichoderma harzianum and ALcaligenes sp. strain AMB 8 applied alone or in combination significantly reduced the incidence of Phytophthora capsici induced nursery rot disease of black pepper. The bacterial strain was able to survive on the stem cutting of black pepper, which is used as planting material. Combined inoculation had '10 effect on the population dynamics of the fungal or bacterial antagonist. The biocontrol agents also improved the root and shoot growth of the plants in the nursery.